Análise da vulnerabilidade ambiental das bacias hidrográficas do litoral sul paraibano - Pires, André Lucena (2015)
The catchment areas of coastal southern state of Paraiba are considered essential, because them are the main sources that are used to supply the metropolitan region of João Pessoa, in the basins of rivers Marés, Mumbaba and Gramame and Mamuaba. Four more captations of streams in the basin of Abiaí-Papocas river were planned, further south, by the Water and Sewerage Company of the State of Paraíba aimed at expanding the supply system that is in operation. These watersheds are located in the meso-regions of Paraíba and Pernambuco Forest, where agriculture, especially the cultivation of sugarcane is the most significant among land uses.. It is desirable that these watersheds, that contributes to the sources of water, presents the best conditions for soil properties and their use in order to maintain the water production capacity and your quality. The analysis of the vulnerability of basins considering the threats arising from the anthropism, it is essential in view of the range of these threats posed mainly by inappropriate land use. Recognizing the importance of conducting diagnostic studies on environmental conditions watershed relating to land use, including the properties of the soil, this research is proposed to build and apply a system of indicators that spatially represents various levels of vulnerability. The proposed system for evaluation of vulnerability watershed, based on use indicators and properties of the soil (SAVIUS), covers the amount of forested areas, riparian forests of the rivers, amount of urban areas and indicators that add more than one variable as the propensity to risk to loss of soil and occurrence of conflicts. A vulnerability rating scale was set to values ranging from zero to one, composed of five classes ranging from very low to very high. The analysis resulting from the application of the proposed system of indicators of vulnerability to the studied basins pointed a percentage of vulnerability High and Very High in 41.66% of the calculated indicators. On the other hand, the percentage of 30.56% of the basins indicators was reached under the classification of vulnerability Low or Very Low. The vulnerability ranked as Average reached the percentage of 27.78%. The results from the applications made for the seven river basins demonstrates the possibilities of the system which is designed to support managers in the process of knowledge of the environmental conditions in the watershed and in the monitoring and implementation of land management programs.